Bakri postpartum balloon: an obstetrician’s armamentarium in managing post-partum haemorrhage - Sharma, Arti; Bansal, Neeta; Ramola, Monika; Chaudhari, Priyanka; Pant, Suman; Panwar, Neha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Post-partum haemorrhage (PPH), an obstetric emergency that can complicate vaginal or cesarean deliveries and associated with serious complications. Guidelines for the management of PPH involve a stepwise escalation of pharmacological and eventual surgical approaches. In women who do not respond to uterotonics or medical treatment, a variety of procedures, such as arterial embolization, surgical ligation of the uterine arteries or obstetric hysterectomy, may be used. The Bakri balloon is an intrauterine device indicated to reduce or control PPH temporarily when conservative treatment is warranted. Here, we are presenting case series of primary atonic PPH and which were managed by Bakri Balloon Tamponade (BBT). Methods: This case series included five women with PPH managed by Bakri balloon as a conservative therapeutic option. Results: All five women were in age group between 23 years to 34 years. The causes of PPH were uterine atony, retained placenta and central placenta previa. The Bakri balloon was successful in controlling hemorrhage in all women (five of five) who did not respond to medical uterotonic treatment. Conclusions: Bakri balloon is a simple, easy to use and effective method for conservative management of acute PPH. This device reduces bleeding, shortens the hospital stay and avoids the need for more aggressive procedures.